Narrative Discourse as a Multi-Level System of Communication: Some Theoretical Proposals Concerning Bakhtin's Dialogic Principle - Paul Thibault (Studies in 20th & 21st Century Literature, 1984)
This article attempts to show that the dialogizing of narrative discourse is a way of de-naturalizing the fictional process and its associated textual activities by reconstituting the material interplay of voices (in Bakhtin's pioneering sense). It is this interplay which is suppressed by the convention of a single, univocal narrative position. This corresponds to Bakhtin's notion of monologic discourse, which implies an already given, objectified identity lying behind the text. Dialogic discourse restores to textual practice the material interplay of frequently opposing and contradictory semantic and ideological positions which actively constitute the formation of discourse. These voices which are constantly re-interpreted and transformed in dialogic discourse will help to show that the Subject is not external to discursive practices, but it is continually re-constituted and transformed within specific discursive formations. The second part of this article contains a detailed analysis of an excerpt from Vladimir Nabokov's novel Ada. Following this are a number of proposals or strategies for understanding the processes of dialogic interaction which take place across levels in the narrative text.
Keywords: dialogizing; narrative discourse; Bakhtin; dialogic principle; monologic discourse; identity; discourse; dialogic discourse; Subject; Vladimir Nabokov; Ada